Frozen Food Quality Control Using Statistical Process Control Methods and Failure Mode and Effect Analysis : Pengendalian Mutu Frozen Food Dengan Metode Statistical Process Control dan Failure Mode and Effect Analysis - Putra, Mochammad Nabil Ferdianto Pratama; Cahyana, Atika Sidhi (Procedia of Engineering and Life Science, 2023)
The research was conducted in UD Mulia Jaya to look out the main causes of defects in frozen food products and to reduce defects in the product of making klasu bread. It is known that the production of klasu bread is 333,490 pcs, product defects are 18,716 pcs, and the average production per day is 6,669 pcs with an average daily product defect of 374 pcs. The defect has exceeded the product defect tolerance limit set by the business owner. The method used Statistical Process Control (SPC) and Failure Mode and Effect Analysis (FMEA). The results showed that the biggest cause of defects was filling out the surface (leaky) with a total of 7,695. Calculation of the Risk Priority Number (RPN) obtained a value of 168. The most dominant factor the environmental factor with recommendations for repairing insulation on each production line to maximize employee performance in reducing product defects.